Microneedles in Drug Delivery: Progress and Challenges - Muhammet Avcil (MDPI AG, 2021)
In recent years, an innovative transdermal delivery technology has attracted great interest for its ability to distribute therapeutics and cosmeceuticals for several applications, including vaccines, drugs, and biomolecules for skin-related problems. The advantages of microneedle patch technology have been extensively evaluated in the latest literature; hence, the academic publications in this area are rising exponentially. Like all new technologies, the microneedle patch application has great potential but is not without limitations. In this review, we will discuss the possible limitations by highlighting the areas where a great deal of improvements are required. Emphasising these concerns early on should help scientists and technologists to address the matters in a timely fashion and to use their resources wisely.